The Persecution and Murder of the European Jews by Nazi Germany, 1933-1945: Volume 2: German Reich 1938-August 1939 - Pearce, Caroline; Heim, Susanne (The Persecution and Murder of the European Jews by Nazi Germany, 1933–1945, 2019)
Frontmatter -- Contents -- Foreword to the English Edition -- Editorial Preface -- Introduction -- List of Documents -- Documents. Tail 1 -- Documents. Tail 2 -- Documents. Tail 3 -- Glossary -- Approximate Rank and Hierarchy Equivalents -- List of Abbreviations -- List of Archives, Sources, and Literature Cited -- Index